Photonic engineering technology for the development of terahertz quantum cascade lasers - Zeng, Yongquan (2020)
A terahertz (THz) quantum cascade laser (QCL) is an electrically pumped semiconductor laser based on the inter-subband electron transitions in a multiple-quantum-well heterostructure. Comparing with many other THz wave generation methods, THz QCL is mostly developed with compact fingerprint, high power, and high efficiency in the demanding frequency range of 0.8–5.4 THz with the aid of advanced electronic engineering technology of the active materials. This triggers various important applications including nonlinear optics, astronomy, imaging, sensing, and spectroscopy. However, the applications of THz QCL require good output characteristics in terms of the emission spectrum, beam quality, power efficiency, and polarization control, which are beyond the reach of the electronic engineering techniques. The main focus here is placed on photonic engineering of the THz QCLs with attention to the significant improvement of THz QCL output characteristics. Various photonic solutions to manipulate the laser output are thoroughly reviewed. Some innovative photonic designs with impressive achievements are highlighted. Nonconventional cavities with exotic physics and special functionalities are also discussed in the end, which may be exploited for potential applications in the future.